Digital synergy for hospitality sustainability: a moderated mediation model of IoT, data-driven decision-making, AI, and hotel sustainable performance - Abdou, Ahmed Hassan; Shehata, Hossam Said (Frontiers in Sustainability, 2026)
IntroductionAs sustainability becomes a strategic priority in the hospitality industry, digital transformation—particularly through the adoption of the Internet of Things (IoT)—offers new opportunities to enhance hotel sustainable performance (HSP). However, the mechanisms and boundary conditions through which IoT adoption improves HSP outcomes remain underexplored, particularly the roles of data-driven decision-making (DDM) and artificial intelligence (AI). Accordingly, this study examines the impact of IoT adoption on hotel sustainable performance, investigates the mediating role of data-driven decision-making, and assesses the moderating role of AI in strengthening these relationships.MethodsGrounded in the Resource-Based View and Dynamic Capabilities Theory, this study analyzed survey data collected from 211 managers working in four- and five-star hotels in Saudi Arabia. Partial least squares structural equation modeling (PLS-SEM) was employed to test the proposed relationships, including the mediating role of data-driven decision-making and the moderating role of artificial intelligence (AI).ResultsThe findings show that IoT adoption positively influences both data-driven decision-making and hotel sustainable performance. Data-driven decision-making partially mediates the relationship between IoT adoption and sustainable performance. In addition, artificial intelligence significantly strengthens the effects of IoT adoption on data-driven decision-making and on sustainable performance.DiscussionThese results demonstrate that integrating IoT with data-driven and artificial intelligence–enabled capabilities enhance hotels' environmental, social, and economic performance. The study contributes to digital sustainability research by clarifying the mechanisms through which IoT creates value and offers practical guidance for hospitality managers seeking to leverage digital transformation to achieve sustainability goals.